HIV Reservoir Characterization Symposium - Eva Malatinkova; Ward De Spiegelaere; Linos Vandekerckhove; Magdalena Sips (Elsevier, 2017)
The HIV Cure Research Center (HCRC) in Ghent organised the first HIV Reservoir Characterization Symposium, and brought together virologists, molecular biologists, immunologists and clinicians to discuss the most recent developments in HIV reservoir characterisation with a view to achieving an HIV cure. The one-day symposium covered new developments in the field of HIV reservoir and HIV cure research, with the latest news on the European HIV cure trials. This report summarises the major themes discussed during the symposium.